Multiculturalism and Multicultural Education in Kurikulum Merdeka - Ella Masita (Universitas Muhammadiyah Semarang, 2023)
This article seeks to investigate how the concepts of multiculturalism and multicultural education are embedded in Kurikulum Merdeka, in particular to the teaching of English at school. This is a qualitative descriptive study in which the curriculum documents ware examined through the application of discourse analysis. Based on the analysis of the texts within the document, the conceptualization of multiculturalism and multicultural education is embedded at the Agency Decree about the expected learning outcomes specifically in the elements of general and advanced English learning as well as English for students with special needs. However, there is a variation of how each element allocate the concepts. The research results also reveal the lack of information relating to the development of multicultural awareness and intercultural development within the learning outcomes for English learning at each phase